Social quality : from theory to indicators - Maesen, Laurent van der; Walker, Alan , 1949- (Palgrave Macmillan, 2012)
This collection sets out the latest research on the concept of 'social quality', developing its theoretical foundations and applying it to pressing policy issues such as the future of the European Union and sustainable global development